Two-stage Anaerobic Digestion of Palm Oil Mill Effluent with Aerobic Post-treatment. - Ismail, Norli (Universiti Sains Malaysia, 2016)
This research investigated the efficiency of combined anaerobic-aerobic treatment system of POME.A series of experiments were conducted to determine the treatment efficiency of anaerobic digestion and aerobic post-treatment of POME at different conditions. Thermophilic anaerobic digester was selected and upgraded to anaerobic contact digester due to its better treatment efficiency and biogas production.